2012
DOI: 10.1111/j.1751-0813.2012.00947.x
|View full text |Cite
|
Sign up to set email alerts
|

Motor neurone disease in molybdenum‐deficient sheep fed the endogenous purine xanthosine: possible mechanism for Tribulus staggers

Abstract: The findings were similar to those observed in sheep with T. terrestris MND, suggesting that the combination of xanthosine ingestion and Mo deficiency may be the cause of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
20
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 15 publications
3
20
1
2
Order By: Relevance
“…The differential regulation of the purines xanthine, hypoxanthine, inosine and AMP under lithium treatment is consistent with the hypothesis of a central role for this pathway in depression [38]. Xanthosine, the corresponding nucleoside of xanthine, has been linked to stagger in sheep, thus associating purine to motor neuron disease [39]. Further, recent studies have shown that ascorbate levels act on the purine metabolism pathway, which suggests that the effect of lithium on ascorbate and purine metabolites that was observed in this study could be linked [40].…”
Section: Discussionsupporting
confidence: 83%
“…The differential regulation of the purines xanthine, hypoxanthine, inosine and AMP under lithium treatment is consistent with the hypothesis of a central role for this pathway in depression [38]. Xanthosine, the corresponding nucleoside of xanthine, has been linked to stagger in sheep, thus associating purine to motor neuron disease [39]. Further, recent studies have shown that ascorbate levels act on the purine metabolism pathway, which suggests that the effect of lithium on ascorbate and purine metabolites that was observed in this study could be linked [40].…”
Section: Discussionsupporting
confidence: 83%
“…In a previous study, xanthosine ingestion by Mo‐deprived sheep was found to be the likely cause of T. terrestris MNS. Unusually, the altered neurotransmission that developed was associated with astrocyte degeneration, not neuronal cell body degeneration.…”
mentioning
confidence: 90%
“…Pasture molybdenum values in the northern hemisphere are typically between 0.9 and 2.6 ppm dry matter, but values as high as 60 ppm have been recorded . In Australia, plant Mo values as low as <0.01 ppm have been associated with outbreaks of a Tribulus terrestris ‐associated motor neurone syndrome (MNS) in sheep . Livestock have physiological mechanisms that prevent dietary sources of these purines from reaching the central nervous system (CNS), because they can exert neuromodulatory effects via an astrocyte‐dependent process that controls the uptake and release of the neurotransmitter glutamate .…”
mentioning
confidence: 99%
See 2 more Smart Citations